1978
DOI: 10.1203/00006450-197804001-00826
|View full text |Cite
|
Sign up to set email alerts
|

821 the Role of Exchange Transfusion (Et) in the Treatment of Severe Septicemia and Sclerema Neonatorum

Abstract: Chronic abdominal pain, c o n s t i p a t i o n , d i a r r h e a , and anorexia arm.often d i f f i c u l t symptoms f o r a p e d i a t r i c i a n t o e v a l u a t e . These c h i l d r e n a r e o f t e n thought t o have psychosomatic complaint It h a s been noted t h a t s t o o l s f o r ova and p a r a s i t e s obtained on some of t h e s e c h i l d r e n have demonstrated p a r a s i t e s o f t e n thought t o be nonpathogenic.Thus, a r e t r o s p e c t i v e e v a l u a t i o n was performed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 0 publications
1
30
2
2
Order By: Relevance
“…Using fresh-frozen plasma as replacement fluid, consumed plasma factors are substituted, thereby possibly restoring the opsonic capacity and improving the coagulation abnormalities, both of which are disturbed in sepsis. Since 1979 several reports have been published on plasmapheresis and whole blood exchange for sepsis [7,8,9,10,11,12,13,14,15,16]. These reports, based on a small number of patients and without appropriate control patients, are inconclusive and conflicting with respect to whether plasmapheresis provides any beneficial effects in the treatment of sepsis.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Using fresh-frozen plasma as replacement fluid, consumed plasma factors are substituted, thereby possibly restoring the opsonic capacity and improving the coagulation abnormalities, both of which are disturbed in sepsis. Since 1979 several reports have been published on plasmapheresis and whole blood exchange for sepsis [7,8,9,10,11,12,13,14,15,16]. These reports, based on a small number of patients and without appropriate control patients, are inconclusive and conflicting with respect to whether plasmapheresis provides any beneficial effects in the treatment of sepsis.…”
Section: Introductionmentioning
confidence: 92%
“…However, the beneficial effect of plasmapheresis is probably not explained solely by the removal of toxic mediators. Using fresh-frozen plasma as replacement fluid, the procedure also replenishes deficiencies such as the immunoglobulins IgM and IgA [11] and coagulation factors and inhibitors such as proteins C and S and antitrombin III. Plasmapheresis may thus restore coagulation abnormalities and improve opsonic capacity and serum bactericidal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The additional use of exchange transfusion (ET), however, has shown promising results in improving outcome of SN with culture-proven septicemia over the past three decades. One study of ET included only preterm infants 25 whereas others [26][27][28][29] included both preterm and term infants. It was concluded that there is increased survival in neonates suffering from SN and sepsis when repeat ET is used early during the course of the disease.…”
Section: Managementmentioning
confidence: 99%
“…ET also improves oxygen exchange by improving the peripheral and pulmonary circulation and shifting the oxygen dissociation curve to the right, and neutralizes endotoxins. [26][27][28][29] Differential diagnosis There are two other diseases of the subcutaneous fat that are important in the differential diagnosis of SN. One of them is SCFN, which occurs in healthy infants, mostly post-term, within a few days to weeks after birth.…”
Section: Managementmentioning
confidence: 99%
“…Surgiu uma variedade de terapêuticas suplementares que podem ser úteis em situações críticas, como no choque séptico, na neutropenia e na hipogamaglobulinemia, no sentido de melhorar os defeitos qualitativos e quantitativos da insuficiência imunólogica neonatal. As modalidades mais importantes são transfusão de granulócitos 37 , exsangüí-neo-transfusão 38,39 , altas doses de imunoglobulina endovenosa 40,41 e, mais recentemente, a administração de citocinas, obtidas pela biologia molecular como anticorpos monoclonais anti-receptores IL-1 e TNF-α 42 e rhG-CSF (fator estimulador de colônias de granulócitos humano) e rhGM-CSF (fator estimulador de colônias de granulócito-macrófago humano) [43][44][45][46] . Antibioticoterapia A seleção de antibióticos deve ser baseada na idade do paciente quando do início da sepse, origem do RN (domiciliar ou hospitalar), história materna, colonização conhecida, situações epidêmicas, entre outros.…”
Section: Tratamentounclassified